Challenges and Opportunity of Housing for Black Miner in South Africa - Olebogeng, David Daw (European Journal of Economics and Business Studies, 2020)
Mine companies are experiencing a change in the political system of the country (South Africa). This political change from apartheid government to the government of Democratic has brought about a totally different system of government; this change has led to the transformation of mines companies from employment section to housing of mineworkers from their operation system, how are the mines companies / houses dealing with this change? Changes in the political and economy of the gold mining in the 1970s - 1980s have prompted management to begin moving away from migratory labour and implementing alternative accommodation strategies for black mine workers. The paper aims to provide some understanding of the current housing situation and housing needs of mineworkers more than a decade after the abolition of the legislation which had shaped the living environments of mineworkers in South Africa, and will look at the different I alternative approaches for housing black mine workers and how they can afford housing.